Efect Of Liquidity and Profitability on Stocks Return with Inflation as a Moderating Variable in Manufacturing companies listed on Indonesia Stock Exchange - Fauji Sanusi; Apriani Wiayanti (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to determine the effect of liquidity as proxied by the current ratio and profitability proclaimed by return on equity on stock returns with inflation as a moderating variable. The sample of this research is 12 manufacturing companies in the food and beverages subsector which are listed on the Indonesian stock exchange for the period 2010- 2018 using the purposive sampling method. From the data processing, partial test get that result liquidity proxied by the current ratio has no effect on stock returns, while the profitability variable proxied by return on equity has a positive and significant effect on stock returns, while the moderate regression analysis test is carried out to obtain inflation results as a moderating variable. Unable to moderate the relationship between liquidity and profitability variables on stock returns.